OPTIMIZATION OF STUDENTS' ACADEMIC ACHIEVEMENT IN SIMPLE FRACTION MATERIAL USING MANIPULATIVE MEDIA IN THIRD-GRADES SOMBRON SDN - Sunarsih, Sunarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research was conducted in response to the observed low learning outcomes among third-grade students at SDN Sombron, particularly in the subject of Mathematics, with a focus on simple fractions. The prevailing teaching and learning methods in these classes predominantly revolved around teacher-centered lectures. Consequently, the research aimed to enhance students' learning outcomes by incorporating concrete instructional media. The study employed the Classroom Action Research (CAR) method, implemented over two cycles. Each cycle encompassed four distinct phases: planning, action (implementation), observation, and reflection. The research involved a total of 15 third-grade students, comprising 6 male and 9 female students, as the study subjects. The findings revealed a noticeable improvement in student learning outcomes when concrete media were integrated into mathematics instruction, specifically in the context of simple fractions. During the initial cycle, 53% of students exceeded the Minimum Completeness Criteria (KKM), equivalent to 8 students. However, in the subsequent cycle, a substantial and remarkable improvement in learning outcomes was observed, with a 100% success rate. In other words, all 15 students surpassed the KKM, indicating the effectiveness of using concrete media in enhancing learning outcomes